Penguatan Branding UMKM Putri Manja di Balikpapan Melalui Repackaging Inovatif dan Pelatihan Visual Digital AI Berbasis Nurance Framework - Ulfah Safira Idris; Sani Gazali; Tiara Dwi Sesaria; Resha Maielyana; Azwandi Azwandi (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
This Community Service Program (PkM) aims to strengthen the branding of MSME Putri Manja in Balikpapan through a structured intervention based on the Nurance Framework. The program addresses major challenges for MSME Putri Manja, including simple packaging designs and suboptimal digital marketing content quality, which hinder competitiveness in the online market. The implementation integrated three core solutions: innovative repackaging, AI-based digital visual training, and social media optimization. The implementation was guided by the Nurance Framework, which upholds the value of "Care" (Kepedulian) and is structured into Conception, Direction, Immersion, and Perception dimensions. The repackaging successfully transformed the product image from a simple home industry to a competitive local brand with a higher selling value. Furthermore, the AI-based digital visual training (using Gemini AI and Chat GPT) effectively increased the digital capacity of the MSME partners. This is evidenced by a significant increase in the average post-test score by 31.3 points (from 55.6 to 86.9) among 25 participants, demonstrating a marked improvement in knowledge and skills in utilizing AI for promotional needs. In conclusion, this program successfully presented a practical implementation model combining physical product improvement and AI technology, which is expected to enhance the competitiveness, market reach, and sales of MSME Putri Manja.